Performance Evaluation of Symmetrical Current Source Multilevel Inverter - et. al., Mr. A. Clement Raj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper proposes a Current Source Multilevel Inverter (CSMLI) with a single rating inductor topology. The multilevel inverters are generally acquainted with power converter's applications because of decreased dv/dt, di/dt stress, and extremely efficient for minimising harmonic distortion in the both output voltage and current. The proposed nine-level current source inverter has analyses under symmetrical operation, and their operation are compared using PI and Fuzzy PI controllers with multicarrier PWM topology. PV utilized as a DC source, photovoltaic energy is an environmentally friendly energy with high potential, simple construction, maintenance, dependability and long life. MATLAB/Simulink simulation has been made for the proposed converter to get its exhibition measures. Some test results are given to confirm the presented Current Source Multilevel Inverter.